STRATEGI MARKETING MIX DALAM MEMPERTAHANKAN HUNIAN KAMAR PADA HOTEL SELYCA MULIA SAMARINDA DIMASA PANDEMI COVID-19 - Uswatun Khoirun Nisa (Sekolah Tinggi Pariwisata Mataram, 2022)
In the marketing strategy there is a set of marketing tools known as the Marketing Mix, namely Product (Product/Service), Price (Price), Place (Location/Place of Distribution Channels), and Promotion (Promotion) are important elements that must be considered in developing and advancing the business. so that the company gets results in accordance with the company's goals. In this study, the researcher used a qualitative descriptive method. This study aims to determine the marketing strategy of Hotel Selyca Mulia in maintaining room occupancy during the covid-19 pandemic and to determine the supporting and inhibiting factors when carrying out marketing activities. The results show that the marketing mix strategy implemented by Selyca Mulia Hotel in terms of product, Selyca Mulia hotel has sold various products such as wedding packages, birthday paries, barbecues, meeting packages and F&B in maintaining room occupancy during the covid-19 pandemic. Then in terms of price, the Selyca Mulia hotel determines the selling price of the room based on the competitor's hotel. Third, in terms of place, the condition of the Selyca Mulia hotel has changed 80%, they apply health protocols for the convenience of visiting guests. Hotel Selyca Mulia also cooperates with OTA (Traveloka) in marketing room products. And finally, in terms of promotion, the media used to promote the Selyca hotel is by using social media such as Instagram, Facebook, and doing personal selling. However, due to the COVID-19 pandemic, sales only use social media as a promotional tool for them to market hotel products. It is known that the inhibiting factor of the marketing strategy is price competition with other four-star hotels. While the supporting factors are offering product prices with appropriate facilities and providing good service to Selyca Mulia hotel guests.